Modified Objective Structured Clinical Examination for Pediatric Interns - Eyal Ben-Isaac; Matthew Keefer; Michelle Thompson (Association of American Medical Colleges, 2013)
Abstract Introduction Objective structured clinical examinations (OSCEs) have traditionally been used by medical schools and residency training programs to assess baseline knowledge. Our objective was to create a medical knowledge assessment tool for pediatric residency training programs which could be easily implemented without the need for a simulation center, ancillary staff, or the use of expensive or technical equipment. Methods Our modified OSCE can be used to assess medical knowledge and clinical competence in a group of trainees. The format is case-based, highlighting the importance of clinical application of theoretical knowledge. A block of approximately 3 hours is needed, with 5 minutes allotted for each station. At the end of the session, all the forms are collected and the program director then spends approximately 90 minutes reviewing each scenario in detail with the entire group. Results Over 300 residents have completed the examination at our institution since the initiation of this educational tool. The annual average class score over the past 15 years of administration has ranged from 50-58 points (with a maximum allowable score of 75). Given that the individual questions and their complexity have been modified every 2-3 years based on the program directors' evaluation of the material, it is impossible for us to compare individual years of data. Discussion We have noted no correlation between individual scores and subsequent performance on standardized examinations; this could due to the differences in format of the exams (case-based written responses versus multiple-choice options). Of interest, anonymous surveys of residents after the exams have repeatedly stated that the experience has been extremely educational and the subsequent discussions foster a positive learning environment.